PENGARUH KARAKTERISTIK KONTEN INSTAGRAM @ALFAGIFT_IDN TERHADAP ONLINE ENGAGEMENT (SURVEY PADA FOLLOWERS INSTAGRAM ALFAGIFT) - Rahmadina, Syafira Fitria; Febriani, Erna (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Today's technological advancements allow social media, such as Instagram, to be an effective tool for disseminating information widely and efficiently. Instagram has become a key platform for companies to conduct promotions and interact with users. Alfagift, one of Alfamart's subsidiaries, utilizes the Instagram account @alfagift_idn to inform about products and promotions. This study aims to measure the effect of Content Characteristics on Online Engagement on the @alfagift_idn Instagram account. With a correlational quantitative approach and survey method, samples were taken from 100 active followers of the account. Descriptive analysis shows that Content Characteristics (Variable X) obtained a value of 82.04%, while Online Engagement (Variable Y) reached 81.54%. The correlation coefficient showed a value of 0.784**, indicating a strong relationship. The coefficient of determination test indicates that 61.5% of the impact on Online Engagement is due to Content Characteristics. Hypothesis testing and simple linear regression showed significance with a value of 0.00 < 0.05 and t-statistic = 12.510, so H0 is rejected and H1 is accepted, confirming a significant influence between Content Characteristics on Online Engagement.